Investigating the utilization of blast furnace flue dusts and mill scale as raw materials in iron nugget production - Birol, Burak (IOP Publishing Ltd, 2019)
Utilization of wastes to produce iron nugget is a value-added process, where the carbon and ferrous oxide contents can be benefited from to produce a high quality byproduct. Present study aims to investigate the usability of blast furnace flue dusts and mill scales in iron nugget production. To achieve this goal, briquettes containing various amounts of blast furnace flue dust (d50 = 187 mu m), with 0%-50% of magnetite concentrate (d50 = 67 mu m), mill scale (d50 = 564 mu m) and ground mill scale (d50 = 74 mu m) were prepared and reduced at 1400 degrees C for 15 min. It was observed that, well metal-slag separation occurred in the briquettes containing 10%-40% of oxide source and they could coalescence to produce iron nuggets. However according to the residual unreacted raw materials, well metal-slag separation, carbon content and microstructure, optimal results were achieved from samples, which contains 30% MC, 40% MC; 30% ground MS and 40% ground MS.
Keywords: blast furnace flue dust; mill scale; iron nugget; carbothermic reduction; REDUCED IRON; ORE PELLETS; SOLID-WASTE; REDUCTION; CARBURIZATION; SLUDGE; Materials Science